Understanding the functions and roles of libraries towards knowledge-based economy / Mohammad Fazli Baharuddin … [et al.] - Baharuddin, Mohammad Fazli; Rahmad, Fadhilnor; Mohd Amin, Zahari; Abu Bakar, Amzari (Faculty of Information Management, 2015)
The knowledge economy is a new concept that has appeared worldwide in recent years. As a sub-discipline of the knowledge economy, knowledge management is a completely new concept and method of management. It works for converting intellectual assets of workers and staff members in the organization into higher productive forces - competition power and new value. The library plays the important roles in order to support knowledge based economy. Therefore, this article focuses on the functions and roles of libraries in supporting knowledge-based economy. Some efforts undertake in Malaysia are also highlighted.